A rare incidence of averting ‘maternal near-miss’ in a case of spontaneous uterine rupture in shock - Biswas, Jayanta K.; Gupta, Sanjaya K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine rupture is a rare but catastrophic obstetric emergency associated with significant feto-maternal morbidity and mortality. There are various risk factors and wide spectrum of clinical presentations have been identified; previous cesarean delivery being most common risk factor. Spontaneous rupture of unscarred uterus is infrequently encountered, but very dangerous for both mother and fetus as remotely suspected. Usually, spontaneous rupture of primigravida uterus is considered almost immune as it is rare but not unheard of; it may occur before or after onset of labour, at term or preterm and with or without fetal heart rate abnormality. The reported case was such a case of spontaneous unscarred uterine rupture with favourable outcome for both mother and baby.